2013
DOI: 10.1161/atvbaha.112.300941
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune Guidance Cue Semaphorin 3E Is Expressed in Atherosclerotic Plaques and Regulates Macrophage Retention

Abstract: Objective The persistence of myeloid-derived cells in the artery wall is a characteristic of advanced atherosclerotic plaques. However, the mechanisms by which these cells are retained are poorly understood. Semaphorins, a class of neuronal guidance molecules, play a critical role in vascular patterning and development, and recent studies suggest that they may also have immunomodulatory functions. The present study evaluates the expression of Semaphorin 3E (Sema3E) in settings relevant to atherosclerosis and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 46 publications
5
107
0
Order By: Relevance
“…15 Recently, it was shown that coronary endothelial cells normally express NTN1, which potently inhibits migration of monocytes in vitro. 26 Our results of downregulation of NTN1 in advanced plaques are supported by the finding that proatherogenic factors (oscillatory shear stress, proinflammatory cytokines) downregulate NTN1 expression in vitro.…”
Section: Circ Cardiovasc Genetsupporting
confidence: 80%
“…15 Recently, it was shown that coronary endothelial cells normally express NTN1, which potently inhibits migration of monocytes in vitro. 26 Our results of downregulation of NTN1 in advanced plaques are supported by the finding that proatherogenic factors (oscillatory shear stress, proinflammatory cytokines) downregulate NTN1 expression in vitro.…”
Section: Circ Cardiovasc Genetsupporting
confidence: 80%
“…Thus, Slit2 could represent an exciting therapeutic candidate to simultaneously inhibit the individual events that collectively promote the initiation and progression of vascular inflammation associated with atherosclerosis. Other guidance cues, such as ephrin B2, netrin1, and semaphorin 3E, are differentially regulated in proatherogenic conditions; however, overall, these factors appear to exacerbate, and not attenuate, progressive vascular injury (47)(48)(49). Further studies are needed to determine whether Slit2 is unique among these cues, preventing early trafficking of monocytes into affected vessels, as we report in this article, as well as advanced lesion progression.…”
Section: Discussionmentioning
confidence: 76%
“…The axon guidance pathways modulate diverse biological phenomena, including cellular adhesion, migration, proliferation, differentiation, survival, and synaptic plasticity, through the participation of highly conserved families of guidance molecules, including netrins, slits, semaphorins, and ephrins, and their cognate receptors 117 and members of these pathways have been highlighted in many recent reports related to macrophage migration, 118 expression of inflammatory markers and M2 signals in atherosclerotic plaque, 119 and chemokine-directed migration of human monocytes. 120,121 Network centrality analysis further identified genes (eg, NCAM1, FYN, and FURIN) likely to play critical roles in the maintenance and functioning of several of the replicated pathways.…”
Section: Systems Genetics Approach To Understanding the Genetic Basismentioning
confidence: 99%